Association of callous traits with reduced neural response to others' pain in children with conduct problems - Lockwood, P; Sebastian, C; McCrory, E; Hyde, Z; Gu, X; De Brito, S; Viding, E (Cell Press, 2013)
Children with conduct problems (CP) persistently violate others’ rights and represent a considerable societal cost [1]. These children also display atypical empathic responses to others’ distress [2], which may partly account for their violent and antisocial behavior. Callous traits index lack of empathy in these children and confer risk for adult psychopathy [3]. Investigating neural responses to others’ pain is an ecologically valid method to probe empathic processing [4], but studies in children with CP have been inconclusive [5, 6]. Using functional magnetic resonance imaging (fMRI), we measured neural responses to pictures of others in pain (versus no pain) in a large sample of children with CP and matched controls. Relative to controls, children with CP showed reduced blood oxygen level-dependent responses to others’ pain in bilateral anterior insula (AI), anterior cingulate cortex (ACC), and inferior frontal gyrus, regions associated with empathy for pain in previous studies [7, 8]. In the CP group, callous traits were negatively associated with responses to others’ pain in AI and ACC. We conclude that children with CP have atypical neural responses to others’ pain. The negative association between callous traits and AI/ACC response could reflect an early neurobiological marker indexing risk for empathic deficits seen in adult psychopathy.